Pharmaceutical price asymmetry and need for a policy framework - T., Senthil Kumar; Sorooshian, Shahryar (IAEME Publication, 2018)
This paper is an opinion in the form of a letter to the editor. Here the authors highlight the issue of pharmaceutical price asymmetry in some countries. The letter explains the need for a comprehensive policy framework in the pricing of pharmaceutical drugs.